Mass spectrometry‐based proteomic analysis of FSCN1‐interacting proteins in laryngeal squamous cell carcinoma cells. Issue 11 (12th July 2019) - Liu, Hongliang; Cui, Jiajia; Zhang, Yuliang; Niu, Min; Xue, Xuting; Yin, Hongyu; Tang, Yemei; Dai, Li; Dai, Fengsheng; Guo, Yujia; Wu, Yongyan; Gao, Wei
Abstract: Fascin actin‐bundling protein 1 (FSCN1) is an evolutionarily conserved actin‐bundling protein that plays a critical role in cell migration, motility, adhesion, and cellular interactions. Although multiple clinical studies have implicated the expression of FSCN1 in laryngeal squamous cell carcinoma (LSCC) progression, the precise mechanism of FSCN1 in the process has not been clearly elucidated. To define FSCN1 function, we characterized FSCN1‐interacting proteins in LSCC cells by immunoprecipitation followed by mass spectrometry (MS). After data filtering, 119 proteins with expression in both the Hep‐2 and TU‐177 cell samples were identified as FSCN1‐interacting partners. With in‐depth bioinformatics analysis, we linked FSCN1 to critical cellular processes including cell adhesion, glycolysis/gluconeogenesis, regulation of protein ubiquitination, ribosomal RNA processing, and small molecule metabolism. We discuss the interactions between FSCN1 and some of the newly validated partners. The identification of these potential partners of FSCN1 expands our knowledge of the FSCN1 interactome and provides a valuable resource for understanding the functions of this protein in LSCC progression.